2012
DOI: 10.1111/ejn.12025
|View full text |Cite
|
Sign up to set email alerts
|

Antisaccades as decisions: LATER model predicts latency distributions and error responses

Abstract: Antisaccades are widely used in the study of voluntary behavioural control: a subject told to look in the opposite direction to a stimulus must suppress the automatic response of looking towards it, leading to delays and errors that are commonly believed to be generated by competing decision processes. However, currently we lack a precise model of the details of antisaccade behaviour, or indeed detailed quantitative data in the form of full reaction time distributions by which any such model could be evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
102
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(105 citation statements)
references
References 35 publications
1
102
2
Order By: Relevance
“…Our computational model uses a modified version of the Linear Approach to Threshold with Ergodic Rate (LATER) (Noorani & Carpenter, 2013); the key modification is that noise in the accumulation process is explicitly modeled. This should not yield qualitatively different interpretations as these models are closely related (Bogacz et al, 2006; Donkin et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Our computational model uses a modified version of the Linear Approach to Threshold with Ergodic Rate (LATER) (Noorani & Carpenter, 2013); the key modification is that noise in the accumulation process is explicitly modeled. This should not yield qualitatively different interpretations as these models are closely related (Bogacz et al, 2006; Donkin et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…1). It is far larger than can be explained by such factors as nerve conduction velocity or synaptic delay: saccadic reaction time essentially represents the time needed to make a decision as to whether a potential target is actually worth looking at (Carpenter 2000), and in recent years the increasing interest in making precise measurements of latency has led to important insights into the neural mechanisms underlying decision (Carpenter 1981;Carpenter and Williams 1995), (Noorani and Carpenter 2013;Schall 2005).…”
Section: Saccadometrymentioning
confidence: 99%
“…Once a particular decision-making unit reaches its threshold, it determines the outcome of the decision by triggering a response. Although initially used to explain simple decision-making tasks, such as looking towards a novel visual stimulus, it has recently been successful in explaining more complex decisions [3][4][5] especially in terms of predicting full reaction time distributions, a very stringent test of any neural model [6].…”
Section: Introductionmentioning
confidence: 99%
“…In this task, a subject is told to look away from, rather than towards, a suddenly-presented visual target, generating anti-saccades instead of the usual pro-saccades, and requiring suppression of the subject's natural tendency to fixate on the target. A recent study has shown [5] that human antisaccade behaviour can be modelled successfully as a race between three distinct decision units: Prosaccade, Antisaccade, and Stop ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation